Dukungan Sosial dan Kemampuan Regulasi Emosi: Studi Korelasional pada Pasien Autoimun - Katlyn Tania; Ivani Krisnacia; Cindy Salim; Rina Mirza; Winida Marpaung (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
People with autoimmune diseases often face complex physical and psychological challenges, including fatigue, pain, uncertainty about disease progression, social misunderstanding, and emotional instability. These conditions require adaptive emotion regulation so that individuals can manage stress, accept their health condition, and maintain psychological well-being. Social support is considered an important external resource that may help individuals cope with chronic illness and regulate their emotional responses more effectively. This study aimed to examine the relationship between social support and emotion regulation among people with autoimmune diseases in Indonesia. A quantitative correlational design was employed. The participants consisted of 97 people with autoimmune diseases selected based on predetermined criteria. Data were collected using a Social Support Scale and an Emotion Regulation Scale. The data were analyzed using Pearson product–moment correlation. The results showed a positive and significant relationship between social support and emotion regulation, with a Pearson correlation coefficient of r = 0.377 and a significance value of p < 0.05. The coefficient of determination indicated that social support contributed 14.2% to emotion regulation, while the remaining 85.8% was influenced by other internal and external factors. Descriptive analysis showed that most participants had high levels of social support, whereas most participants’ emotion regulation was in the moderate category. These findings indicate that although social support plays a significant role, it is not sufficient by itself to optimize emotion regulation among people with autoimmune diseases. The study highlights the need for psychological interventions that not only strengthen social support but also develop structured emotion regulation skills. These findings provide practical implications for counselors, families, health professionals, and support communities in promoting adaptive coping, emotional resilience, and psychological well-being among people living with autoimmune diseases.